2022
DOI: 10.3390/biomedicines10030699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Interest of Serum Alpha-2 Macroglobulin, Apolipoprotein A1, and Haptoglobin in Patients with Non-Alcoholic Fatty Liver Disease, with and without Type 2 Diabetes, before or during COVID-19

Abstract: In patients with non-alcoholic fatty liver disease (NAFLD) with or without type 2 diabetes mellitus (T2DM), alpha-2 macroglobulin (A2M), apolipoprotein A1 (ApoA1), and haptoglobin are associated with the risk of liver fibrosis, inflammation (NASH), and COVID-19. We assessed if these associations were worsened by T2DM after adjustment by age, sex, obesity, and COVID-19. Three datasets were used: the “Control Population”, which enabled standardization of protein serum levels according to age and sex (N = 27,382)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 102 publications
1
3
0
Order By: Relevance
“…We then plotted the adjusted mean of A2M as a function of age and T2DM status. As in Poynard et al study, 3 we found that A2M progressively increased with age. However, we still found significantly higher levels of A2M in patients with T2DM aged 45-70 years.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We then plotted the adjusted mean of A2M as a function of age and T2DM status. As in Poynard et al study, 3 we found that A2M progressively increased with age. However, we still found significantly higher levels of A2M in patients with T2DM aged 45-70 years.…”
supporting
confidence: 85%
“…Following the comments of Poynard et al, 1 we pursued the analysis in our dataset by using their approach. However, rather than comparing A2M in different subgroups that does not allow to control for several factors in the same analysis, 3 we considered all together the potential confounding factors they explored by calculating the A2M mean adjusted on age, sex, body mass index, and histologic parameters (fibrosis stage, steatosis grade, and an inflammatory activity score corresponding to the sum of lobular inflammation and ballooning grades). Results showed that adjusted mean of A2M was significantly higher in patients with T2DM (226 mg/dL; 95% confidence interval, 219-233) as compared with those without (208 mg/dL; 95% confidence interval, 201-215; P ¼ .001).…”
mentioning
confidence: 99%
“…Previous studies have reported that the XCL1 [182], HLA-DMB [183], CD40 [184], HLA-DRA [185], RUNX1 [186], IL18R1 [187], NINJ2 [188], ACE (angiotensin I converting enzyme) [189], CD44 [190], IL4R [191], MYD88 [192], WNT9B [193], CXCL16 [194], CXCL13 [195], RORB (RAR related orphan receptor B) [196], GDF15 [197], THEMIS (thymocyte selection associated) [198], KCNH7 [199], BTK (Bruton tyrosine kinase) [200] and MOBP (myelin associated oligodendrocyte basic protein) [201] are a key regulators of multiple sclerosis. Recently, increasing evidence demonstrated that HLA-DMB [202], VIP (vasoactive intestinal peptide) [203], GATA6 [204], CD40 [205], TFAP2B [206], HFE (homeostatic iron regulator) [207], IGFBP7 [208], NPY2R [209], CCL2 [210], AQP5 [211], HLA-DMA [212], RUNX1 [81], PPY (pancreatic polypeptide) [213], ASPA (aspartoacylase) [214], NOS1 [215], ADAM12 [216], NPPC (natriuretic peptide C) [217], COL1A1 [218], IL1R1 [219], ABCG2 [220], ACE (angiotensin I converting enzyme) [221], CD34 [222], HLA-DPA1 [223], A2M [224], MEOX2 [225], CDKN2A [226], SERPINE1 [227], CD44 [228], FABP4 [108], ITGB3 [229], ALOX5AP [230], SFRP4 [231], ISM1 [232], IL4R [233], RUNX2 [234], CASP1 [235], CCR4 [236], MYD88 [237], DRD3 [238], STAT6 [239], ANXA1 [240], CAV1 [241], RGS4 [242], SPHK1 [243], CYP2C8 [244], CD163 [245], DIRAS3 [131], POSTN (periostin) [246], SELL (selectin L) [247], TMPRSS2 [248], CXCL16 […”
Section: Discussionmentioning
confidence: 99%
“…The first article is a narrative review, which provides an overview of the most recent studies that determine type 2 diabetes mellitus as a risk factor and link it to poor prognosis of COVID-19 [ 16 ]. The second one assessed how alpha-2 macroglobulin, apolipoprotein A1, and haptoglobin are associated with the risk of liver fibrosis, inflammation, and COVID-19 in patients with non-alcoholic fatty liver disease with or without type 2 diabetes mellitus [ 17 ].…”
mentioning
confidence: 99%